Cyclic hematopoiesis: the mechanism of cyclic neutropenia in grey collie dogs - Dale, David C. (1972)
Two grey collie dogs had regular cyclic fluctuations in the number of all formed elements of the blood. The period lengths for all elements for an individual dog were the same, but the pattern of fluctuation for each element was distinctive. Normal dogs lacked periodic fluctuations. The patterns of day-to-day variation in the normal dogs counts were consistent with a first-order autoregressive process of serial dependence (i.e., each observation of the series depends on the last preceding observation and no others). The grey collie counts showed the same pattern of serial dependence after the component of the over-all variability due to cyclic oscillation was removed. These data suggest that a defect of hematopoietic regulation at the stem cell level leads to periodic interruptions of production of all hematopoietic elements and accounts for the cycles seen in the peripheral blood counts.